Geomagnetic solar-diurnal variations at the Antarcticа, the relationship with solar activity - Maksimenko, O. I.; Shenderovska, O. Ya (Ukrainian Antarctic Journal, 2014)
According to the monitoring of variations of the geomagnetic field over the period 1958-1991, Sq-variation amplitudes of horizontal and vertical components of the magnetic field depending of the index F10.7 have been studied at the Ukrainian Antarctic station ’AIA’ . Against the background of the high correlation r (Sq; F10.7) = 0,72-0,92 using regression analysis to determine the increase of inclination (’a’) of the regression line in the summer and on the growth phase of the solar cycle, annual (summer and winter) fluctuations (’b’) daily amplitude of Sq-variations upon minimal F10.7. It was found that the ratio ’a / b’ for Z, Y component of the field is not constant, as is customary in the spherical harmonic model Sq (CM4), and in addition shows emissions in some months and the change of sign in the winter. Diagrams of annual changes monthly empirical values of diurnal amplitudes SqY, SqZ variations and index F10.7, are reflecting their similarity in the years of maximum CA and a cyclic characteristics during 33 years on the AIA.